EFEKTIFITAS ALAT TRIGONAL PENCIL DALAM PENINGKATAN MENULIS PADA ANAK KESULITAN BELAJAR DI SDN 20 KALUMBUK PADANG - Joni Effendi (Universitas Negeri Padang, 2015)
This research is motivated by problems in a child's learning difficulties third class in SDN 20 Kalumbuk who have difficulty in writing so that even if the child is in third class he was not able to write well. Under theseconditions, the researchers want to prove that the use of Trigonal Pencil tools can boost children's writing skills in third grade learning difficulties in SDN 20 Kalumbuk. This study uses a Single Subject Research approach, with desian A –B- A and data analysis techniques using visual analysis chart.fungtions this study indicate that Trigonal Pencil tools is able to improve the writing skills of learning difficulties for children third class at SDN 20 Kalumbuk PadangKata Kuci : Kesulitan Belajar ; kemampuan ; Menulis ; Trigonal Pencil